DFIG Topologies for DC Networks: A Review on Control and Design Features - Marques, Gil D.; Iacchetti, Matteo Felice (IEEE transactions on power electronics, 2019)
The doubly fed induction machine has been traditionally adopted in adjustable-speed ac power generation drives in order to take advantage of the reduced rating for the power electronic interface. Aside this well-established application where the doubly fed induction generator (DFIG) is controlled by a back-to-back converter, recent literature records a growing interest toward un-conventional DFIG drives for dc power generation, combining DFIG high control freedom with simplified power electronic interfaces to achieve an overall cheap and fully controllable system. Despite several concepts have been demonstrated on small-scale rigs, there is a lack of systematic comparison among different topologies and control solutions. This paper bridges this gap by providing a review of recent topologies, their control, design and performance, and operation issues. As major novelties, this paper includes off-spec performance comparison of different torque-ripple mitigation strategies, discussion of sizing requirements for generator and power electronics, fundamental aspects of the behavior under voltage dips, and priorities and challenges for future research on the subject.